2023
DOI: 10.1101/2023.01.05.522933
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dihydroxy-Metabolites of Dihomo-gamma-linolenic Acid Drive Ferroptosis-Mediated Neurodegeneration

Abstract: Even after decades of research, the mechanism of neurodegeneration remains understudied, hindering the discovery of effective treatments for neurodegenerative diseases. Recent reports suggest that ferroptosis could be a novel therapeutic target for neurodegenerative diseases. While polyunsaturated fatty acid (PUFA) plays an important role in neurodegeneration and ferroptosis, how PUFAs may trigger these processes remains largely unknown. PUFA metabolites from cytochrome P450 and epoxide hydrolase metabolic pat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…In this study, it is noteworthy to highlight that certain compound, including metabolites derived from DGLA, three distinct isomeric forms of EpEDE, and DHED, were successfully synthesized and comprehensively characterized for the very first time. As a result, the incorporation of these oxylipins in our method enables us to determine these important lipids in C. elegans , like DHED which induces neurodegeneration and ferroptosis, 11 thereby contributing valuable insights to the quantitative lipidomics and targeted metabolomics field.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, it is noteworthy to highlight that certain compound, including metabolites derived from DGLA, three distinct isomeric forms of EpEDE, and DHED, were successfully synthesized and comprehensively characterized for the very first time. As a result, the incorporation of these oxylipins in our method enables us to determine these important lipids in C. elegans , like DHED which induces neurodegeneration and ferroptosis, 11 thereby contributing valuable insights to the quantitative lipidomics and targeted metabolomics field.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 ( Figure 1 ) Our recent study also indicated that dihydroxyeicosadienoic acid (DHED), an epoxide hydrolase metabolite of dihomo-gamma-linolenic acid, induces degeneration of dopaminergic neurons through ferroptosis, which could affect aging. 11 However, the exact role of oxylipins in neurodegeneration and whether they play any critical role in aging remains elusive. 20 Therefore, investigating whether aging has any effects on the oxylipins level and vice versa will help to develop more effective preventative measures and treatments for age-related diseases, including neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, dysregulation of ferroptosis can promote the development of multiple human diseases (Y. Jiang, Qiao, et al, 2023;Sarparast et al, 2023;. Researchers have shown increasing enthusiasm for the role of ferroptosis in cancer development.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…In this issue of ACS Central Science, Alan, Lee, and co-workers report a new class of lipid metabolite that regulates neurodegeneration through ferroptosis. 3 Ferroptosis is a regulated mechanism of cell death that relies on iron and reactive oxygen species to catalyze lipid peroxidation preferentially in polyunsaturated fatty acids (PUFAs, Figure 1A). 4 PUFAs are long-chain fatty acids that contain at least two double bonds and are classified as omega-3 (ω-3) or omega-6 (ω-6) based on the position of the first double bond relative to the methyl carbon.…”
mentioning
confidence: 99%